Local attitudes and perceived threats of human elephant conflict: a case study at Lake Jipe, Kenya - Maureen W Kinyanjui; Naiya R Raja; Ewan J Brennan; Lucy E King; Lydia N Tiller (Pachyderm)
Opportunity costs of human–elephant conflict are complex and pose diverse challenges to both humans and elephants, whether real or perceived. In the Lake Jipe area, on the western boundary of Tsavo West National Park in Kenya, people see elephants in their vicinity almost daily. This expanding community is facing complex challenges as fishing, the main source of income, has declined substantially and the community is becoming more aware of the presence of elephants. We conducted a rapid rural appraisal using semi-structured interviews and questionnaires within three lakeside fishing villages to better understand how these changes within the community, and how tensions among stakeholders are affecting interactions with elephants. The results were complemented by data from two years of GPS tracking data of an elephant that was frequently present in the communities. Perceptions and attitudes of the community towards elephants were analysed and the ‘conflict to coexistence continuum framework’ was applied to determine the state in which this community exists in relation to elephants. Our findings suggest that worsening socioeconomic issues such as unsustainable income sources, food insecurity and human–human tensions play an important role in influencing risk perceptions and increasing perceived conflicts with elephants. In the three villages studied, risks and benefits, and relations among stakeholders are likely to determine whether community interactions with elephants shift towards coexistence or conflict. We argue that the increasingly vulnerable livelihoods observed in these communities may shift the villagers' position within the continuum towards one of intolerance and conflict with elephants in the future.